Teacher’s Mental Health in Students Perspective and Its Contribution to Student’s Achievement of Islamic Religious Studies - Nurbaiti, Nurbaiti (TAZKIYA Journal of Psychology, 2020)
The purpose of this study is to determine teacher’s mental health according to student’s perspective and its contribution to student’s achievement in Islamic Religious Studies. The study was conducted at Azhari Elementary School of Jakarta and involved 52 students as research participants, with a stratified simple random sampling. This research used test and questionnaire as instruments to collect data. The data validity by correlation coefficient of point biserial (r pbi) and correlation coefficient of product moment (r xy). The data reliability by KR 21 and alpha cronbach (a). The results proved, the teacher’s mental health contributed 54 % to student’s achievement of Islamic religious studies.